A Conceptual Metaphor on the Intellectual System of Naeem Farasheri - Seyad Ali Ghasemzadeh (مطالعات زبانی و بلاغی)
A negative outcome of modernism or relying on modernist epistemology is to suppose material nature as a dead body. Modern human, while struggling to benefit and survive, not only fights with fellow human beings, but also ruins nature as is one of his obstacles. Among attempts of scholars in different domains, to concern such an epistemic crisis about nature, a review on the thoughts of mystic poets and artists can be beneficial culturally and cognitively. This research, using a descriptive-analytic method and relied on hermeneutic approach which tries to have a review on the intellectual system of Naeem Farasheri, the great Albanian Persian poet. The research, studies his thought about the beliefs of cosmic sense, and imagining the universe as an alive creature, to represent basic discourse propositions of his world-view and poetic style. The results of the research show that Naeem Farasheri, inspired by epistemological principles of Iranian-Islamic Mysticism and Sufism, and benefiting from intellectual and artistic system of Iranian great poets, such as Rumi and Attar, who uses conceptual metaphors like, “nature is human, and human is nature” and frequently addresses the universe as an alive creature.